Selective As(v) capture by a novel magnetic green Fe-biochar composite in a packed column: An application of central composite design - Sawood G.M.; Dixit S.; Mishra G.; Gupta S.K. (My University, 2025)
Arsenic contamination in groundwater is a prominent global issue due to its substantial toxicological impacts on the environment and human health. Herein, a fixed-bed column experiment was carried out for feasibility analysis of using a novel Fe-impregnated Azadirachta indica biochar matrix for arsenate removal. The adsorbent was characterized by SEM, EDAX, BET, XRD, TGA, VSM, and XPS analysis. Statistical RSM with central composite design is applied to examine the synergistic effects of process parameters on the adsorption of arsenate. A high R2 value of 0.994 predicted by ANOVA established the adequate regression of the proposed model. At a bed height of 18.0 cm, flow rate of 3.0 mL min-1, pH 7 and initial arsenate concentration of 500 µg L-1, the arsenate uptake capacity of Fe-AIB was found to be 149 µg g-1. Various mathematical models including the Thomas, Yoon Nelson, Adams-Bohart and BDST models were used to analyse the column experiment data. The Thomas model best defines the nature of the breakthrough curves at various conditions. The BDST model manifested good agreement with experimental results and obtained high R2 values, showing the significant applicability of this model for the current fixed-bed column system. The regeneration of columns was conducted using 10% NaOH. © The Royal Society of Chemistry.